Vanishing Perturbations of Hyperbolic Equations - Correia, Joaquim M.C. (2015)
Well-posedness of the initial value problem u_t+f(u)_x=\eps u_xx -\del((u_xx)^2)_x; u(x,0)=u_0(x). Then, as \eps, \del tend to 0, we prove convergence of the previous solutions to the entropy weak solution of the initial value problem u_t+f(u)_x=0; u(x,0)=u_0(x).